Progress in the treatment of Alzheimer’s disease is needed: position statement of European Alzheimer’s Disease Consortium (EADC) Investigators - Jessen, Frank; Kramberger, M. G.; Angioni, D.; Aarsland, D.; Balasa, M.; Bennys, K.; Boada, M.; Boban, M.; Chincarini, A.; Exalto, L.; Felbecker, A.; Fliessbach, K.; et al. (The journal of prevention of Alzheimer's disease, 2024)
β-amyloid-targeting antibodies represent the first generation of effective causal treatment of Alzheimer’s disease (AD) and can be considered historical research milestones. Their effect sizes, side effects, implementation challenges and costs, however, have stimulated debates about their overall value. In this position statement academic clinicians of the European Alzheimer’s Disease Consortium (EADC) discuss the critical relevance of introducing these new treatments in clinical care now. Given the complexity of AD it is unlikely that molecular single-target treatments will achieve substantially larger effects than those seen with current β-amyloid-targeting antibodies. Larger effects will most likely only be achieved incrementally by continuous optimization of molecular approaches, patient selection and combinations therapies. To be successful in this regard, drug development must be informed by the use of innovative treatments in real world practice, because full understanding of all facets of novel treatments requires experience and data of real-world care beyond those of clinical trials. Regarding the antibodies under discussion we consider their effects meaningful and potential side effects manageable. We assume that the number of eventually treated patient will only be a fraction of all early AD patients due to narrow eligibility criteria and barriers of access. We strongly endorse the use of these new compound in clinical practice in selected patients with treatment documentation in registries. We understand this as a critical step in advancing the field of AD treatment, and in shaping the health care systems for the new area of molecular-targeted treatment of neurodegenerative diseases.
Online veröffentlicht: 11. August 2024
Gesehen am 04.11.2024